The Onion Book of Known Knowledge - Editor-in-Chief: Randazzo, Joe (New York Little, Brown & Company, 2012)
Compiled and Organized According to the Higher Principles of Intellectual Commerce and Coercion for the Betterment of Mankind and the Zweibel Family, Specifically.
Include Illustrations.
A Definitive Encyclopaedia of Existing Information : In 27 Excruciating Volumes.
Keywords: American wit and humor -- Handbooks, vade-mecums, etc